Case Report: A 91-Year-Old Patient With Non-Small Cell Lung Cancer Harboring MET Y1003S Point Mutation - Gao, Beili; Zeng, Ran (Frontiers in Medicine, 2022)
Background: The Y1003S point mutation in exon 14 of MET is a rare mutation that can lead to oncogenic transformation. Few data are available about the characteristics of this mutation. This report presents an elderly NSCLC patient with the Y1003S mutation in MET detected by next-generation sequencing (NGS). Case report: In October 2020, a 91-year-old male was admitted to the Department of Respiratory and Critical Care Medicine, Ruijin Hospital, due to increased carcinoembryonic antigen. Imaging revealed highly suspicious lesions in the right upper lobe lung, right apex, and left upper lobe with the traction of the adjacent pleura. The patient was histologically confirmed adenocarcinoma, and MET Y1003S mutation was detected by NGS subsequently. After evaluation, the patient started crizotinib treatment in December 2020. In the first assessment of tumor response, a chest computed tomography (CT) scan in January 2021 showed partial response. The patient experienced pulmonary embolism and abnormal liver function during the treatment and recovered after symptomatic treatment. He maintained partial response at the last available assessment in July 2021, with the right upper lung lesion being 26×9 mm. Conclusion: MET Y1003S mutation was detected in this case, and the patient achieved partial response using crizotinib. This case highlighted the role of NGS in detecting a rare mutation. Successful remission of complications in such an elderly patient necessitates careful and timely management.